Impact of Early Clinical Exposure on Communication Skills and Confidence Levels in Pre-Clinical Medical Students - Muhammad Tauseef Javed, Anum Wahid, Bilal Masood, Azal Jodat, Qaiser Masud Sheikh, Abeer Anjum (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Early clinical exposure (ECE) is an evolving educational strategy that integrates real or simulated clinical experiences into the early years of medical training. It is designed to enhance professional development, improve communication, and increase confidence among medical students. However, evidence from South Asian medical institutions remains limited. Objective: To evaluate the impact of early clinical exposure on communication skills and confidence levels among undergraduate medical students across all academic years. Methodology: A cross-sectional observational study was conducted from February 2022 to January 2023 involving 100 MBBS students enrolled from first to fifth year. Participants were equally divided into two groups: one with structured ECE and the other with no early exposure. A validated, self-administered questionnaire assessed communication and confidence domains using a 5-point Likert scale. Data were analyzed using SPSS version 26.0. Independent t-tests and Chi-square tests were applied, with p < 0.05 considered significant. Results: Students in the ECE group scored significantly higher in communication (mean: 4.31 ± 0.46) compared to the non-ECE group (mean: 3.65 ± 0.59; p < 0.001). Similarly, confidence levels were greater among ECE students (mean: 4.17 ± 0.49 vs. 3.51 ± 0.58; p < 0.001). Improvements were consistent across all academic years. Conclusion: Early clinical exposure significantly enhances communication skills and clinical confidence among undergraduate medical students. Integration of ECE into pre-clinical curricula is recommended to improve student preparedness and foster professional competence. Keywords: Early clinical exposure, communication skills, confidence, undergraduate medical education, medical students, clinical competence